Technology and Production Process of Bajau Traditional Pottery in Pulau Selakan Semporna - Ayob, Norhayati; Shamsu, Mohamad (School of Social Sciences, USM, 2017)
This paper aims to provide an initial background of the process of making traditional ceramic pottery of culture heritage. Ceramic pottery is one of the hallmarks of Sabah’s heirloom, not only use as cooking and storage containers but also closely linked with folk cultures and heritage. The Bajau Laut ethnic community of Semporna or better known as the Sea Gypsies, mostly are boat dwellers and work as fishermen in the coast. Therefore, this research aims to explore the traditional pottery making in Sabah, by investigating the background history of Lapohan pottery. This study is also based on the chronological process of making pottery and taboos of the process of preparing the clay, forming, decoration technique, motif application and firing techniques. The relevant information for the study will be gathered from field study, including observation, in-depth interview and video recording. In-depth interviews will be conducted with several potters and the conversation and pottery making process will be recorded in order to understand the actual process of making Lapohan.